Climate Change and Agriculture - Hussain, Saddam (IntechOpen, 2019)
Climate change is likely to have an extensive impact on agriculture around the world through changes in temperature, precipitation, and CO2 concentration. This book provides the most recent research on the interaction between climate change and the agriculture sector. With contributions from internationally recognized scientists, this volume contains 13 chapters covering the key topics related to climate change hazards, risk assessment, mitigation strategies, and climate-smart agriculture innovations. It offers a solid foundation for the discussion of climate resilience in agricultural systems and the requirements to keep improving agricultural production in the face of mounting climate challenge. All the agriculturists, environmentalists, climate change specialists, policy makers, and research scholars will find this remarkable volume a welcome addition to their collection.